The cultural institutionalization of photography in France: a brief history - Yacavone, Kathrin (Edinburgh University Press, 2014)
This article provides a historical overview of the cultural institutionalization of photography in France, with a particular focus on the pioneering initiatives of individual photography enthusiasts throughout the 1970s to promote photographic culture. These efforts were roughly simultaneous with changes in acquisition and exhibition practices on the part of fine art museums and collections with respect to photography, in response to an increasing world-wide recognition of its status as an art form. The article explains how, despite the promotion of photography as a French invention and a contribution to culture (as early as its inception in 1839), an active cultural politics of photography did not emerge until the early to mid-1980s and was an opportune reaction to, and institutionalized framing of, ground-level cultural developments already underway.